Efforts to Regenerate Batik Makers in Surakarta City through the Social Capital of Kampung Batik Laweyan - Indah Puspitasari*; Yosafat Hermawan Trinugraha; Bagas Narendra Parahita (Riwayat: Educational Journal of History and Humanities, 2024)
Batik is an intangible oral cultural heritage of Indonesia whose existence needs to be preserved. The preservation of batik in relation to the survival of generations capable of becoming batik makers is an important urgency. Given the sustainability of cultural identity will be maintained through inheritance from generation to generation. The purpose of this study is to identify and analyze the strategy of maintaining the young generation of batik makers in Surakarta City with a focus on the utilization of social capital in Laweyan Batik Village. This research was conducted in Laweyan Batik Village which is the largest and oldest batik production center in Surakarta City. The research method used is a descriptive qualitative research method. The researcher used Robert Putnam's social capital theory with its 3 main elements, namely networks, norms, and trust. The results showed that social capital in Kampung Batik Laweyan plays a crucial role in supporting batik regeneration. The network of Kampung Batik Laweyan formed through FPKBL enables cooperation. Norms that include work systems and flexibility of rules with the principle of kinship frame behavior. The close network and norms foster trust, enabling effective coordination in the regeneration process.